2016
DOI: 10.3847/0004-637x/830/2/143
|View full text |Cite
|
Sign up to set email alerts
|

MILLIMETER TRANSIENT POINT SOURCES IN THE SPTpol 100 SQUARE DEGREE SURVEY

Abstract: The millimeter transient sky is largely unexplored, with measurements limited to follow-up of objects detected at other wavelengths. High-angular-resolution telescopes, designed for measurement of the cosmic microwave background (CMB), offer the possibility to discover new, unknown transient sources in this band-particularly the afterglows of unobserved gamma-ray bursts (GRBs). Here, we use the 10 m millimeter-wave South Pole Telescope, designed for the primary purpose of observing the CMB at arcminute and lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Although the sky is regularly monitored across many bands of the electromagnetic spectrum (as well as in gravitational waves and energetic particles) the dynamic sky at millimeter to sub-millimeter wavelengths (0.1-10 mm) remains poorly explored. There has only been one blind transient survey specific to the millimeter band 1 (Whitehorn et al 2016); millimeter facilities are usually only triggered after an initial discovery at another wavelength. Even when targeting known transients, the success rate for detection is low, and only a few extragalactic transients 2 .…”
Section: The Transient Millimeter Skymentioning
confidence: 99%
“…Although the sky is regularly monitored across many bands of the electromagnetic spectrum (as well as in gravitational waves and energetic particles) the dynamic sky at millimeter to sub-millimeter wavelengths (0.1-10 mm) remains poorly explored. There has only been one blind transient survey specific to the millimeter band 1 (Whitehorn et al 2016); millimeter facilities are usually only triggered after an initial discovery at another wavelength. Even when targeting known transients, the success rate for detection is low, and only a few extragalactic transients 2 .…”
Section: The Transient Millimeter Skymentioning
confidence: 99%
“…Afterglows often have a spectral peak in or near the mm range [117], with emission lasting over days to weeks. One candidate object with properties broadly consistent with a GRB afterglow was tentatively detected by Whitehorn et al [119] on SPT data over 100 deg 2 with an observing time of 6,000 h, but the statistical significance of the detection was too low to completely rule out a fluctuation. GRB emission is expected to be less tightly beamed at these wavelengths than in gamma-rays.…”
Section: The Extragalactic Transient Skymentioning
confidence: 96%
“…Telescopes designed for observations of the cosmic microwave background (CMB) are optimized for wide-field surveys, operate at millimeter wavelengths, and have a typical observing strategy in which a patch of sky up to thousands of square degrees is reobserved regularly, making them powerful instruments for transient surveys (Holder et al 2019). Whitehorn et al (2016) performed the first transient survey with a CMB experiment using SPTpol, the second-generation camera on the South Pole Telescope (SPT), and found one transient candidate with no apparent counterpart. Recently, the Atacama Cosmology Telescope (ACT) serendipitously discovered three flares associated with stars (Naess et al 2021) similar to those previously observed by Brown & Brown (2006), Beasley & Bastian (1998), Massi et al (2006), Salter et al (2010), andBower et al (2003).…”
Section: Introductionmentioning
confidence: 99%